Zinc status in athletes: relation to diet and exercise - Micheletti, A.; Rossi, R.; Rufini, S. (Sports Medicine, 2001)
Zinc is involved in the biochemical processes supporting life, such as cellular respiration, DNA reproduction, maintenance of cell membrane integrity and free radical scavenging. Zinc is required for the activity of more than 300 enzymes, covering all 6 classes of enzyme activity. Zinc binding sites in proteins are often of distorted tetrahedral or trigonal bipyramidal geometry, made up of the sulphur of cysteine, the nitrogen of histidine or the oxygen of aspartate and glutamate, or a combination. Zinc in proteins can either participate directly in chemical catalysis or be important for maintaining protein structure and stability. The nutritional habits of elite athletes during training and competition are quite different from the recommended diet in the majority of the population. Endurance athletes often adopt an unusual diet in an attempt to enhance performance: an excessive increase in carbohydrates and low intake of proteins and fat may lead to suboptimal zinc intake in 90% of athletes. Mild zinc deficiency is difficult to detect because of the lack of definitive indicators of zinc status. In athletes, zinc deficiency can lead to anorexia, significant loss in bodyweight, latent fatigue with decreased endurance and a risk of osteoporosis.